Optimalisasi Ketahanan Masyarakat Dalam Masa Pandemi Covid-19 Melalui Penerapan Teknologi Tepat Guna Di Desa Cileungsi Kidul Bogor - Prayudi Prayudi (Sekolah Tinggi Teknik - PLN, 2022)
The problem of community resilience during the Covid-19 pandemic and the extraordinary event of dengue fever, which often occurs during the rainy season, is often faced by the community and a solution must be found. Dastana Kampung Tangguh Lodaya RW15 is one solution so that villages that can independently adapt and deal with potential disaster threats can increase community resilience. The problem is public awareness of the risk of non-natural disasters as well as the facilities and infrastructure to prevent the spread of the plague epidemic optimally. One of the solutions from the P2M activities of the Faculty of Technology and Business Energy ITPLN is to carry out socialization activities and training on the use of appropriate technology to increase community resilience. The result is Dastana Kampung Responsibility Lodaya said that outreach and training activities can increase community resilience, the use of appropriate technology can prevent the spread of outbreaks and the covid-19 pandemic that can cause non-natural disasters